# SOLUTION: There are two trees in a garden, tree A and tree B and on both tress are some birds. The birds of tree A say to the birds of tree B that if one you comes to our tree, then our po

Algebra ->  Algebra  -> Polynomials-and-rational-expressions -> SOLUTION: There are two trees in a garden, tree A and tree B and on both tress are some birds. The birds of tree A say to the birds of tree B that if one you comes to our tree, then our po      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Polynomials, rational expressions and equations Solvers Lessons Answers archive Quiz In Depth

 Question 620947: There are two trees in a garden, tree A and tree B and on both tress are some birds. The birds of tree A say to the birds of tree B that if one you comes to our tree, then our population will be the double of yours. Then the birds of tree B tell the birds of tree A that if one of you comes here then our poplation will be equal to that of yours. How many birds are in each tree?Answer by ankor@dixie-net.com(15649)   (Show Source): You can put this solution on YOUR website!There are two trees in a garden, tree A and tree B and on both trees are some birds. The birds of tree A say to the birds of tree B that if one you comes to our tree, then our population will be the double of yours. Then the birds of tree B tell the birds of tree A that if one of you comes here then our population will be equal to that of yours. How many birds are in each tree? : let a = original number of birds in tree A leg b = original number of birds in tree B : "The birds of tree A say to the birds of tree B that if one you comes to our tree, then our population will be the double of yours." a + 1 = 2(b - 1) a + 1 = 2b - 2 a = 2b - 2 - 1 a = 2b - 3 : "Then the birds of tree B tell the birds of tree A that if one of you comes here then our population will be equal to that of yours." a - 1 = b + 1 a = b + 1 + 1 a = b + 2 replace a with (2b-3), from the 1st statement 2b - 3 = b + 2 2b - b = 2 + 3 b = 5 birds on tree B, originally then a = 5 + 2 a = 7 birds on tree A : : Check these solutions in the equation a = 2b - 3 7 = 2(5) - 3 7 = 10 - 3